1995
DOI: 10.1080/07391102.1995.10508823
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Effectors and DNA Structure: Effect of Glycine on Precipitation of DNA by Multivalent Cations

Abstract: We have investigated the effect of glycine (an organic osmolyte) on DNA precipitation induced by spermine4+, spermidine3+ and Tb3+ addition, using circular dichroism (CD), UV spectroscopy (UV), and electric linear dichroism (ELD) techniques. DNA precipitation by the three compounds is perturbed by glycine: more spermine4+, spermidine3+ and Tb3+ must be added to obtain the same extent of precipitation as compared to the behaviour in absence of this organic osmolyte. It seems that glycine has a general effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
4
16
1
Order By: Relevance
“…The above predictions from the TBI theory are in accordance with the experimental observations (31,35,96,106,107). In the experiments, the addition of methanol, alcohol, and urea may influence not only the dielectric constant (the polarization of solvent molecules), but also the ion-binding specificity (hydrogenbond mediated ion-nucleic acid interaction).…”
Section: Dielectric Constant Dependence Of Helix-helix Attractionsupporting
confidence: 84%
See 1 more Smart Citation
“…The above predictions from the TBI theory are in accordance with the experimental observations (31,35,96,106,107). In the experiments, the addition of methanol, alcohol, and urea may influence not only the dielectric constant (the polarization of solvent molecules), but also the ion-binding specificity (hydrogenbond mediated ion-nucleic acid interaction).…”
Section: Dielectric Constant Dependence Of Helix-helix Attractionsupporting
confidence: 84%
“…Various experiments have demonstrated the important role of the dielectric property of solvent in DNA condensation (31,35,96,106,107). For example, experiments have shown that the addition of methanol in solvent favors the ion-mediated DNA condensation and aggregations (31,35,96).…”
Section: Dielectric Constant Dependence Of Helix-helix Attractionmentioning
confidence: 99%
“…Cellular loss of organic osmolytes does not only contribute to cell shrinkage but may favour destabilization of proteins and may thus participate in the dismantling of the cell during apoptosis [5,7,14]. However, without specific inhibitors the contribution of taurine release to any event of apoptosis cannot be evaluated adequately.…”
Section: Discussionmentioning
confidence: 97%
“…Organic osmolytes stabilize proteins, counteracting the adverse effects of inorganic and organic ions [1,7,8,10,12,22,38,39]. Possibly, destabilization of proteins participates in the disintegration of apoptotic cells.…”
Section: Discussionmentioning
confidence: 98%